The hollow crown. [videorecording (DVD)] The complete series : Richard II, Henry IV part 1, Henry IV part 2, Henry V - Eyre, Richard, 1943-; Shakespeare, William, 1564-1616 (Córdova, Zoraida., 2013)
The Hollow crown: New adaptations of Shakespeare's tetralogy of history plays comprising the 'Henriad' for the BBC's 2012 Cultural Olympiad: King Richard; II King Henry IV, Part 1; King Henry IV, Part 2 and King Henry V. The plays chronicle a continuous period in British history from the end of the 14th century to the aftermath of the Battle of Agincourt in 1415. Together, the plays comprise a story with recurring themes of power struggles, redemption, family conflict and betrayal -- IMDB.